METHODOLOGICAL PECULIARITIES OF DOMAIN ASSESSMENT OF INTERNATIONAL CLASSIFICATION OF FUNCTIONING, DISABILITY AND HEALTH THAT IS USED IN PHYSICAL THERAPY, ERGOTHERAPY - Savchenko, V. M.; Kharchenko, H. D.; Kerestei, V. V.; Buriak, O. Yu.; Pohrebniak, Yu. M. (Rehabilitation and Recreation, 2023)
Introduction. The World Health Organization recommends the rehabilitation specialists to use the International Classification of Functioning, Disability and Health (ICF), which allows describing a patient’s condition based on all components of health and related problems that limit a patient’s life activity. However, the use of ICF in a real clinical practice is associated with certain difficulties. Purpose: to define and describe the methodological approaches to the assessment of ICF domains/categories used in physical therapy, ergotherapy. Material and methods. The material of the study was methodological techniques of practical activity, ICF domains / categories, intended for direct or indirect characterization of human motor activity, the violation of which is diagnosed and restored by a physical therapist, an ergotherapist. Results. The data on difficulties of using the ICF in a real rehabilitation practice are given. Such difficulties are: 1) establishing in each specific clinical case the number of domains sufficient for an acceptable level of description of a patient’s functioning, activity and participation; 2) correct application of domain assessment tools. In order to achieve the compliance of various tools for assessing the state of human health to objective essence and dimension of assessment scale of the ICF components it is expedient: 1) to use an assessment tool without alteration, if its conclusion meets the requirements of the unified-standard scale of quantitative assessment of ICF domains/categories; 2) in cases of partial unconformity of conclusion made with help of an assessment tool of the ICF scale it must be modified (to increase or decrease in the number of gradations, to establish the direction of interpretation of changes in violations); 3) in cases of complete unconformity of conclusion made with help of an assessment tool of the ICF it is necessary to develop the assessment scale for such tool of the ICF that would correspond to the ICF; 4) In case of necessary to build up the own or essentially modify the existing assessment scales, we should consider that the number of gradations always amounts to 5, and the gradations are constructed within the range of the minimum and maximum possible values of the parameter (indicator, signs), the limits of each gradation are established by applying percentage of changes characteristic of degree of manifestation of the problem (absent – 0–4%, light – 5–24%, moderate – 25–49%, severe – 50–95% and absolute – 96–100%). Conclusions. Methodological approaches to the creation of a unified assessment toolkit of ICF domains/ categories used in physical therapy and ergotherapy have been developed. A unified assessment system of ICF domains/categories for physical therapists and ergotherapists is proposed.